Challenges Faced by Arabic Language Teachers in Designing Lesson Plans (RPP) at Madrasah Aliyah: an Exploratory Study on Instructional Planning - Hanna Qoyyimah; Khoirunnisa Ridwani; Salman Raesatria (Gunung Djati Conference Series, 2026)
This study aims to deeply explore various factors that influence the process of Arabic language teachers in designing Lesson Plans (RPP) at Madrasah Aliyah. Employing a descriptive qualitative approach, the research provides an in-depth depiction of the challenges faced by Arabic teachers in preparing lesson plans. Data were collected through interviews, observations, and documentation, supported by curriculum documents and relevant regulations. The analysis followed the Miles, Huberman, and Saldana model through iterative stages of data reduction, data display, and conclusion drawing. The findings present a holistic picture of the dynamics of instructional planning and reveal that teachers face complex challenges, including diverse student abilities, administrative workload, limited time, and technical constraints related to digital tools. These difficulties affect their ability to formulate objectives, select materials, choose appropriate methods and media, and develop effective assessments. Teachers respond to curriculum demands in varied ways some view them as flexible guidelines, while others perceive them as administrative burdens. Limited resources, heavy workloads, and insufficient training further exacerbate these challenges. To address them, teachers adopt adaptive strategies such as utilizing teacher working groups (MGMP), simplifying lesson plans, using simple digital platforms, and engaging in collaboration. The institutional context of the madrasah also shapes the quality of planning, making institutional support essential.